Evaluation of Lure Traps to Capture Adult Red Palm Weevil (Rhynchophorus ferrugineus) at the Date Palm Orchards of Sindh, Pakistan: Lure Traps to Rhynchophorus ferrugineus at Date Palm - Ranjhan Junejo; Nida Shams Jalbani; Asif Ali Bhatti; Muhammad Usman Shar; Ismail Murat Palabiyik; Ashfaque Ali Bhatti; Fakhar-un-Nisa Memon; Ayaz Ali Memon; Shahabuddin Memon (Biological Sciences - PJSIR, 2024)
This study deals with the field application of lure traps for trapping of the adult red palm weevil (Rhynchophorus ferrugineus) at the date palm orchard of Sindh, Pakistan. The pheromone traps, were installed at the date palm orchard under the field conditions such as aggregation pheromone dosage, food material (molasses), ester (isoamyl acetate) and trap density. During the field trials, it was observed that the 3 mg/trap dose of aggregation pheromone along with the 500 g of molasses and 4 mg/trap of ester trapped maximum female adult insects. The 10 traps/ha was the optimized trap density. Moreover, the higher number of insects were trapped in March and the minimum catches were observed in the month of November, December, January and February. The total male and female adult weevils captured were (N=18 females 60% and N=12 males 40%) and the sex ratio was 2:3 male and female, respectively.